2009
DOI: 10.1016/j.ijsu.2008.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient general surgical follow-up: Are we using this resource effectively?

Abstract: Over 50% attendances (21/41) for 'normal' results could have been avoided by the use of a directed informative letter. Outpatient clinics are an important resource whose usage must be optimised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…1 The national figure for nonattendance at outpatient clinics in the United Kingdom is 12%, but there are large variations between specialties and regions. 2 Factors associated with nonattendance in prior studies include illness, work commitments, transportation difficulties, and forgetfulness.…”
mentioning
confidence: 99%
“…1 The national figure for nonattendance at outpatient clinics in the United Kingdom is 12%, but there are large variations between specialties and regions. 2 Factors associated with nonattendance in prior studies include illness, work commitments, transportation difficulties, and forgetfulness.…”
mentioning
confidence: 99%
“…Alternatives for post-operative follow-ups for benign pathology results are being explored to create more time for outpatient clinic visits for new patients. About 50% of the attendances could be avoided for recurrent patients with normal test results, with the potential to optimize outpatient clinic resources [14]. Both Bromage et al and Gurjar et al use the earlier mentioned elementary alternatives to create a more efficient outpatient clinic visits.…”
Section: More Efficient Post-operative Follow-ups In Other Surgical Smentioning
confidence: 99%
“…In a retrospective review of outpatient attendances to general surgery clinics in a district general hospital in the UK, Gurjar et al reported that 22% of clinic attendances were for benign post operative follow-ups and they felt that more than half of these were unnecessary. 1 If we could reduce the number of patients seen unnecessarily then there could be more time to see new patients.…”
Section: Is Routine Surgical Patient Follow-up Required?a Ns_5498 767mentioning
confidence: 99%
“…Both techniques have been already described. 1,2 Seventy-four patients, who refused or were not indicated for the above mentioned techniques, underwent standard LC via four trocars. The six NOTES transvaginal cholecystectomies were performed as planned without complications within an average of 65 min.…”
Section: The Medico Legal Issuesmentioning
confidence: 99%
See 1 more Smart Citation